Electrical Properties of ZnS Thin Films - Hasan, Bushra A. (Iraqi Journal of Physics, 2009)
The effect of annealing temperature (Ta) on the electrical properties like ,D.C electrical conductivity (σ DC), activation energy (Ea),A.C conductivity σa.c ,real and imaginary (ε1,ε2) of dielectric constants ,relaxation time (τ) has been measured of ZnS thin films (350 nm) in thickness which were prepared at room temperature (R.T) using thermal evaporation under vacuum . The results showed that σD.C increases while the activation energy values(Ea) decreases with increasing of annealing temperature.(Ta) from 303- 423 K .The density of charge carriers (nH) and Hall mobility (μH) increases also with increasing of annealing temperature Hall effect measurements showed that ZnS films were n-type converted to p-type at high annealing temperature(423K).Measurements of a.c conductivity over frequency range (102-106Hz) showed that a.c conductivity obeys the formula σ a.c(w)= A ws,where (s) lies between (0.6- 0.95), σ a.c(w) declared exponentially dependence on the frequency range.